Are recent changes in the terrestrial small mammal communities related to land use change? A test using pellet analyses. Issue 5 (22nd May 2015) - Torre, Ignasi; Gracia‐Quintas, Laura; Arrizabalaga, Antoni; Baucells, Jordi; Díaz, Mario
Abstract: Human‐induced landscape changes are expected to have strong effects on the composition and structure of terrestrial small mammal communities (Orders Rodentia and Soricomorpha). However, testing such expectations is difficult due to low detectability of these animals. We used analyses of barn owl ( Tyto alba ) pellets sampled in the same roosting places during 1977–1991 and again in 2011–2014 to (a) document small mammal community changes and (b) relate them to changes in land use. Forest and synanthropic small mammals increased by a 7 % between both periods, whereas open‐land species decreased by 13 %. Man‐made loss (crops and meadows) and expansion (forest and urban) of relevant habitat types were closely related to these changes. Localities with land use changes opposite to the general trend showed also an opposite trend in small mammal community change. Land use heterogeneity increased and dominance decreased between both sampling periods, and this pattern was paralleled by an increasing trend in diversity and a decreasing trend in dominance in small mammal communities. Decreasing trends of some generalist northern species with restricted ranges may have been due to climate change. Diet monitoring of barn owls are thus valuable tools for both documenting and analyzing fine‐grained small mammal responses to global change.